Tasa de supervivencia de los implantes dentales de óxido de circonio. Una revisión sistemática y metaanálisis - Arbildo-Vega, Heber Isac (2017)
ABSTRACT Background: Although titanium is a popular material in implantology, its greyish colour can lead to aesthetic problems. Therefore, research has focused on finding a material for implants that has the same colour of the tooth, in order to improve its aesthetic appearance, and at the same time is highly biocompatible and able to withstand the forces present in the oral cavity. Objective: To determine the survival rates of zirconium oxide dental implants, using a systematic review and meta-analysis. Material and methods: A literature search was conducted up to December 2015 in the biomedical databases, PubMed, Scopus, Web of Science, and Google Scholar. The selection criteria of the studies considered to use zirconium oxide dental implants, with a maximum age of 5 years, that reported survival rates, time greater than or equal to one year follow-up, and a sample size equal to or greater than 10 patients. The methodological quality of the studies was analysed using the JADAD and CMQ scales. Results: The search strategy resulted in 13 articles, in which the overall survival rate was 91.43%, with a follow up of between 1 and 5 years. Conclusion: The literature reviewed suggests that zirconium oxide dental implants have the same survival rate than titanium dental implants, however more research is needed to recommend clinical use.